A Case Study On Social Performance On Amanah Ikhtiar Malaysia : “Reaching The Bottom Billion” - Abdul Zalim, Siti Nazariah (2009)
Microcredit programn1e is developed to provide financing access to the poor so that they can increase their income and improve their living conditions. Mikrokredit ialah program pemberian pinjaman kepada golongan miskin agar mereka dapat n1enggunakan pinjaman tersebut untuk menjana pendapatan dan meningkatkan taraf hidup.